The Republic of Kazakhstan in the System of International Regional Integration Associations - Shkurkin, Dmitry V.; Ryazantsev, Sergey V.; Gusakov, Nikolay P.; Andronova, Inna V.; Bolgova, Viktoriya V. (International Review of Management and Marketing, 2016)
Nowadays the Republic of Kazakhstan is a member of many international and regional economic and political organizations such as the United Nations, the World Bank, the International Monetary Fund, the Customs Union, the Eurasian Economic Community customs union, the OSCE, the Shanghai Cooperation Organization, and so on. Kazakhstan is a country ready to cooperate and participate in regional integration with neighboring states. Kazakhstan in the region of Central Asia is an initiator and leader of all integration processes, is ready to a constructive dialogue with regional and international political and economic partners. Experience of the development of integration processes in various countries with adequate answers to many important problems, the collective effectuation of sovereignty is the most optimal way of assurance of national interests and real independence in the modern interconnected world. Participation of smaller, less developed and militarily powerful states in regional integration associations furnishes them a guarantee and real chance to counteract a policy of dictate, pressure and violence more effective. Therefore, the prevention of threats to national security is the key priority in security in the region of Central Asia. Keywords: integration processes, regional integration, economic cooperation, Central Asia JEL Classifications: F02, F15, O53, N85